Incarnation and Resurrection - lntellectus Quaerens Fidem - Janka, Filemon (Filozofia Chrześcijańska, 2013)
This article discusses two events from Jesus Christ’s life: incarnation and resurrection. They constitute a problem in philosophy. These events in the light of Christian faith do not require the type of epistemological reasons, because it is the mystery of faith. In philosophy, however, up to this day they are analyzed by many philosophers and are getting rationalization. These events  are a scandal for the modern philosophy, in the words of Pope Benedict XVI in his book Jesus of Nazareth, and counterpoint to the contemporary, as Cardinal Gianfranco Ravasi said.